Academic Motivation of Students Experiencing Person-Environment Misfit in Social Work Educational Settings: The Role of Social Dominance Orientation - Alessio Tesi; Daniela Di Santo; Antonio Aiello (European Journal of Investigation in Health, Psychology and Education, 2024)
Interweaving social dominance, person-environment fit, and self-determination theories, the present study sought to understand whether the attrition between students’ levels of social dominance orientation and the hierarchy-attenuating function of the social work faculty in which they study may influence students’ academic motivational pathways. A total of 221 undergraduate social work students participated in the study and completed a self-report questionnaire. Participants’ social dominance orientation, person-environment misfit, and academic intrinsic and extrinsic motivation were measured. Results indicated that students’ social dominance orientation was associated with an external rather than an internal regulation of their academic motivation, mediated by their perceived person-environment misfit. For those students who personally support group-based inequalities, exposure to hierarchy-attenuating contexts would lead to regulating their academic behavior toward the pursuit of extrinsic (vs. intrinsic) goals, that is, studying to gain financial benefits and social prestige, in accordance with the pursuit of their beliefs of social dominance.